Optimalisasi Petunjuk Jalan untuk Meningkatkan Aksebilitas di Desa Nalela, Kecamatan Porsea, Kabupaten Toba - Gunawan B Simangunsong; Fajar Putra E Gulo; Hirenimus Herman Giawa; Pendamaian Duha; Rivanto H Simanjuntak; Atalisi Zalukhu (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This service aims to optimize road signs in Nalela Village, Porsea District, Toba Regency, to improve accessibility for the community. Accessibility is an important factor in regional development, as it reflects how easily people can reach public services and economic opportunities. The research method used in this service article is descriptive qualitative, by conducting direct observation, in-depth interviews, and data analysis to understand the real conditions in the field. The results of the service showed that although most of the roads in the village were well paved, the lack of clear road signs resulted in confusion among road users. In this work program, HKBP Nommensen University KPPM students designed and installed informative and easy-to-understand road signs. This service successfully demonstrated that optimizing road signs can improve people's understanding in using the road and reaching various facilities. Hopefully, the results of this service can be a reference for similar efforts in other rural areas in Indonesia, so that accessibility becomes one of the priorities in regional development.